The puzzle place: Leon's antics - Fujimoto, Michi (New York : Putnam & Grosset Group, 1995)
Ben shares his new ant farm with the Puzzle Place. The direction include a warning: DO NOT OPEN. But Leon can't resist the temptation- and soon the ants take actions have consequences and that he has to take responsibility for the
Based on the teleplay, "Roamantics," by Ellis Weiner, Cris Franco and Joseph A. Bailey
Keywords: Ants-Stories; Children's stories